The global burden, trends, and inequalities of individuals with developmental and intellectual disabilities attributable to iodine deficiency from 1990 to 2019 and its prediction up to 2030 - Yang, Xuesong; Liu, Cheng; Liu, Yanbo; He, Zhigang; Li, Juan; Li, Yijing; Wu, Yanqiong; Manyande, Anne; Feng, Maohui; Xiang, Hongbing (Frontiers in Nutrition, 2024)
Using data from the Global Burden of Disease (GBD) 2019, we conducted a cross-country inequity analysis to examine the worldwide burden of developmental and intellectual disabilities caused by the re-emerging issue of iodine deficiency from 1990 to 2019. After summarizing the latest evidence, we also made predictions up until the year 2030. According to our results, we observed a significant decline in age-standardized prevalence and annual Years Lived with Disability (YLD) rates during this period. Data analysis indicates that females are more susceptible, with adolescents being particularly vulnerable. Geographic distribution also suggests that areas with lower Socio-Demographic Index (SDI) are most severely affected. A correlation emerged between higher SDI and lower prevalence rates, highlighting the role of economic and social factors in the disease's incidence. The cross-national inequity analysis demonstrates that despite improvements in health inequalities, disparities still exist. Projections, in addition, show that the burden of disease is likely to head into a decline until 2030. This research underscores the necessity for targeted interventions, such as enhancing iodine supplementation and nutritional education, especially in areas with lower SDI. We aim to provide a foundation for policymakers to further research effective preventative and potential alternative treatment strategies.